Functional Brain Correlates of Upper Limb Spasticity and Its Mitigation following Rehabilitation in Chronic Stroke Survivors. (2nd July 2014) - Pundik, Svetlana; Falchook, Adam D.; McCabe, Jessica; Litinas, Krisanne; Daly, Janis J.
Abstract : Background. Arm spasticity is a challenge in the care of chronic stroke survivors with motor deficits. In order to advance spasticity treatments, a better understanding of the mechanism of spasticity-related neuroplasticity is needed. Objective. To investigate brain function correlates of spasticity in chronic stroke and to identify specific regional functional brain changes related to rehabilitation-induced mitigation of spasticity. Methods. 23 stroke survivors (>6 months) were treated with an arm motor learning and spasticity therapy (5 d/wk for 12 weeks). Outcome measures included Modified Ashworth scale, sensory tests, and functional magnetic resonance imaging (fMRI) for wrist and hand movement. Results. First, at baseline, greater spasticity correlated with poorer motor function (P = 0.001 ) and greater sensory deficits (P = 0.003 ). Second, rehabilitation produced improvement in upper limb spasticity and motor function (P < 0.0001 ). Third, at baseline, greater spasticity correlated with higher fMRI activation in the ipsilesional thalamus (rho = 0. 49, P = 0.03 ). Fourth, following rehabilitation, greater mitigation of spasticity correlated with enhanced fMRI activation in the contralesional primary motor (r = - 0. 755, P = 0.003 ), premotor (r = − 0. 565, P = 0.04 ), primary sensory (r = − 0. 614, P = 0.03 ), and associative sensory (r = − 0. 597, P = 0.03 ) regions while controlling for changes in motor function. Conclusions. Contralesional motor regions may contribute to restoring control of muscle tone in chronic stroke.